2022
DOI: 10.3390/ijerph192113836
|View full text |Cite
|
Sign up to set email alerts
|

How Has COVID-19 Impacted Our Language Use?

Abstract: The COVID-19 pandemic has led to severe consequences for people’s mental health. The pandemic has also influenced our language use, shaping our word formation habits. The overuse of new metaphorical meanings has received particular attention from the media. Here, we wanted to investigate whether these metaphors have led to the formation of new semantic associations in memory. A sample of 120 university students was asked to decide whether a target word was or was not related to a prime stimulus. Responses for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A large word association study by Laurino et al [ 34 ] found that even in a relatively short time, the company that words keep can change, finding that as compared to the words used before the COVID-19 pandemic, words used during the pandemic led to new associations, such as the word strain , which in pre-COVID associations had more frequently been associated with wine , while during the pandemic it found itself in the company of decidedly less Bacchic neighbors, including mutations and antibiotics . Indeed, similar results were found in several other COVID related studies, reinforcing the speed with which semantic drift can erode and reform the semantic landscape [ 35 37 ]. But semantic drift is far from limited to large scale, environmental change, and is as normal an occurrence in the blogosphere [ 38 ] as it is in many a regular conversation [ 39 ].…”
Section: Related Worksupporting
confidence: 85%
“…A large word association study by Laurino et al [ 34 ] found that even in a relatively short time, the company that words keep can change, finding that as compared to the words used before the COVID-19 pandemic, words used during the pandemic led to new associations, such as the word strain , which in pre-COVID associations had more frequently been associated with wine , while during the pandemic it found itself in the company of decidedly less Bacchic neighbors, including mutations and antibiotics . Indeed, similar results were found in several other COVID related studies, reinforcing the speed with which semantic drift can erode and reform the semantic landscape [ 35 37 ]. But semantic drift is far from limited to large scale, environmental change, and is as normal an occurrence in the blogosphere [ 38 ] as it is in many a regular conversation [ 39 ].…”
Section: Related Worksupporting
confidence: 85%
“…Only few empirical studies have looked at the effects of imagery on the recipient during the COVID-19 pandemic and it is therefore still an open question, how imagery affects the perception of the pandemic. Pisano and colleagues ( 27 ) demonstrated that participants had formed new semantic associations (e.g., “trench”—”hospital”) during the pandemic, that were stronger and more readily available than classical associations (e.g., “trench”—”soldier”). Further research showed that, by experimentally creating and comparing different news articles about the pandemic, the inclusion of metaphors in the articles predicted greater self-efficacy in readers ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, higher levels of anxiety, depression, and stress have been recorded during the confinement period compared to the pre-COVID-19 emergency, disrupting the balance of daily activities and the perception of well-being in both healthy people [ 16 , 17 , 18 , 19 , 20 ] and people with neurological conditions [ 21 , 22 , 23 , 24 ]. Lockdown measures imposed during the COVID-19 pandemic also caused cognitive changes in different populations [ 20 , 25 , 26 , 27 , 28 ]. For instance, in Nogueira et al’s study [ 28 ], a deterioration of cognitive flexibility and processing speed compared to pre-COVID-19 confinement was detected in a group of healthy subjects.…”
Section: Introductionmentioning
confidence: 99%